Nonparametric identification and estimation with non-classical errors-in-variables - Kirill S. Evdokimov; Andrei Zeleneev (Centre for Microdata Methods and Practice (cemmap), 2024)
This paper considers nonparametric identification and estimation of the regression function when a covariate is mismeasured. The measurement error need not be classical. Employing the small measurement error approximation, we establish nonparametric identification under weak and easy-to-interpret conditions on the instrumental variable. The paper also provides nonparametric estimators of the regression function and derives their rates of convergence.
Keywords: 330; Nonparametric procedure; Statistical error; Regression analysis; Estimation theory; Nichtparametrisches Verfahren; Statistischer Fehler; Regressionsanalyse; Schätztheorie